1-1-12 one-step wash-in scheme for desflurane low flow anesthesia: performance without nitrous oxide - Sathitkarnmanee T; Tribuddharat S; Nonlhaopol D; Thananun M; Somdee W (Dove Medical Press, 2015)
Thepakorn Sathitkarnmanee, Sirirat Tribuddharat, Duangthida Nonlhaopol, Maneerat Thananun, Wilawan Somdee Department of Anesthesiology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Background: We reported a 1-1-12 wash-in scheme for desflurane-nitrous oxide (N2O) low flow anesthesia that is simple, rapid, and predictable. There remain some situations where N2O should be avoided, which limits the generalizability of this wash-in scheme. The objective of our study was to determine the performance of this scheme in contexts where N2O is not used.Methods: We recruited 106 patients scheduled for elective surgery under general anesthesia. After induction and intubation, wash-in was started with a fresh gas flow of air:O2 1:1 L/min and a vaporizer concentration of desflurane of 12%. Controlled ventilation was then adjusted to maintain PACO2 at 30–35 mmHg.Results: The alveolar concentration of desflurane (FAD) rose rapidly from 0% to 6% in 4 minutes in the same pattern as observed in our previous study in which N2O was used. An FAD of 7% was achieved in 6 minutes. An FAD of 1% to 7% occurred at 0.6, 1, 1.5, 2, 3, 4, and 6 minutes. The rise in heart rate during wash-in was statistically significant, although not clinically so. There was a slight but statistically significant decrease in blood pressure, but this had no clinical significance.Conclusion: Performance of the 1-1-12 wash-in scheme is independent of the use of N2O. Respective FADs of 1%, 2%, 3%, 4%, 5%, 6%, and 7% can be expected at 0.6, 1, 1.5, 2, 3, 4, and 6 minutes. Keywords: low flow anesthesia, wash-in, desflurane, air